2015
DOI: 10.1177/0300060514561135
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled clinical trial evaluating multiplex polymerase chain reaction for pathogen identification and therapy adaptation in critical care patients with pulmonary or abdominal sepsis

Abstract: The LightCycler® SeptiFast PCR test demonstrated a significant reduction in the time required for initial pathogen identification, compared with standard BC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 27 publications
(47 reference statements)
0
43
0
Order By: Relevance
“…45,69,[71][72][73][74][75][76][77][78][80][81][82][83][85][86][87][90][91][92][93][94][96][97][98][99][101][102][103]107,[109][110][111][112]114 Of these, nine studies reported blood volumes that did not comply with CE approval: Lehmann et al, 76 Lodes et al 92 and von Lilienfeld-Toal et al 71 all reported using 1 ml in adults; Bloos et al, 74 Lamoth et al, 75 Paolucci et al 99 and Sitnik et al 107 all reported using 3 ml in adults; Berger et al…”
Section: Details Of Index and Reference Tests Blood Sampling Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…45,69,[71][72][73][74][75][76][77][78][80][81][82][83][85][86][87][90][91][92][93][94][96][97][98][99][101][102][103]107,[109][110][111][112]114 Of these, nine studies reported blood volumes that did not comply with CE approval: Lehmann et al, 76 Lodes et al 92 and von Lilienfeld-Toal et al 71 all reported using 1 ml in adults; Bloos et al, 74 Lamoth et al, 75 Paolucci et al 99 and Sitnik et al 107 all reported using 3 ml in adults; Berger et al…”
Section: Details Of Index and Reference Tests Blood Sampling Methodsmentioning
confidence: 99%
“…The setting across the remaining studies varied (see Table 4). Explicit inclusion and exclusion criteria for patients were reported for seven SeptiFast studies, 74,80,83,106,[110][111][112] (confidential information has been removed) and one IRIDICA study. 116 With the exception of the SeptiFast study by Warhurst et al, 111 which reported on health-care-associated bloodstream infections, and the SeptiFast study by Josefson et al, 85 which reported on community-acquired bloodstream infections, reporting of whether infection was community or hospital acquired was unclear in the remainder of the included studies.…”
Section: Study Design Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations